ANFIS and PI based performance analysis of three phase three wire distribution system for THD reduction - Sreejyothi, Khammampati R.; Jayakumar, J.; Kumar, P. Venkatesh (International Journal of Applied Power Engineering (IJAPE), 2025)
Due to the rising usage of nonlinear loads and power electronic devices in businesses, one of the key power system concerns today is inadequacy of power quality (PQ). This article presents compensation of current harmonics in distribution system in source side by using adaptive neuro fuzzy inferences system (ANFIS) controller. DSTATCOM optimized proportional integral (PI) controller and ANFIS regulator are utilized for DC link voltage regulation. The ANFIS controller showed better performance compared to PI controller during compensating harmonics time. This paper compared two control schemes results PI and ANFIS. Three-phase three-wire inverter is used for DSTATCOM circuit. In the results compared DC capacitor voltage and total harmonic distortion (THD) values of source current. The THD with PI controller is 7.92% while by using ANFIS controller it is reduced to 2.76%. The concert of proposed method is analyzed with MATLAB/Simulink software.